Analisis Perancangan Mesin Pemotongan Wire Berbasis Automatic Wire Cutting MC di PT. Mitsuba Indonesia - Yudhi Chandra Dwiaji (Politeknik Negeri Samarinda, 2020)
Stator Generator is a stator that uses a generator consisting of a coil and a magnet that emits an alternating voltage so that it can rotate the flywheel, the stator generator is a product of the development of the Stator Motor whose production demand is always increasing. The Stator Generator consists of Flywheel Assy and Stator Comp. In the Manufacture Stator Comp process, the longest production process is wire cutting. This research started from finding the problem of long production time. In the process of cutting wire, it is still done manually using cutting pliers by the production operator. To meet daily production needs, this wire cutting process requires two employees to carry out the production process with an ever-increasing target. From these problems, a wire cutting machine based on Automatic Wire Cutting was developed in order to get maximum and efficient production results. Calculations in material selection and cutter angle are also considered so that the results of the wire cutting process are stable and produce good cuts.